2014
DOI: 10.1039/c4tc00749b
|View full text |Cite
|
Sign up to set email alerts
|

New multifunctional phenanthroimidazole–phosphine oxide hybrids for high-performance red, green and blue electroluminescent devices

Abstract: Two novel fluorescent materials containing phenanthroimidazole/diphenylphosphine oxide possessing bipolar charge-transporting property have been used not only as emitters to fabricate high-performance deep-blue OLEDs, but also as hosts to fabricate highly efficient green and red PhOLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 88 publications
6
111
0
Order By: Relevance
“…Kassner et al [34] and Wang et al [63] reflected this result in their reported phase diagrams. Other authors [64] did not find any evidence of constitutional defects and claim that perfect stoichiometry is in effect.…”
Section: Formation Energies In Al 4 Usupporting
confidence: 51%
“…Kassner et al [34] and Wang et al [63] reflected this result in their reported phase diagrams. Other authors [64] did not find any evidence of constitutional defects and claim that perfect stoichiometry is in effect.…”
Section: Formation Energies In Al 4 Usupporting
confidence: 51%
“…Notably, when substituted position of phenyl is changed between anthracene and imidazole for p-PABPI and m-PABPI, the efficiency is changed by approximately three times, which results from the higher PL quantum yields of p-PABPI and the significantly improved carrier injection/transport ability of p-PABPI (Fig. S9) [30]. Interestingly, when luminance is up to 1000 cd m À2 , the current efficiency for p-PABPI-based devices still maintain an upward trend.…”
Section: Electroluminescent Propertiesmentioning
confidence: 92%
“…2. The triplet energy level of DYNS evaluated from the highest-energy vibronic sub-bands [31] was 2.45 eV, which was identical to that of DYSN.…”
Section: Optical Propertiesmentioning
confidence: 99%